2012
DOI: 10.1523/jneurosci.2775-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

The β-Secretase-Derived C-Terminal Fragment of βAPP, C99, But Not Aβ, Is a Key Contributor to Early Intraneuronal Lesions in Triple-Transgenic Mouse Hippocampus

Abstract: Triple-transgenic mice (3xTgAD) overexpressing Swedish-mutated ␤-amyloid precursor protein (␤APP swe ), P310L-Tau (Tau P301L ), and physiological levels of M146V-presenilin-1 (PS1 M146V ) display extracellular amyloid-␤ peptides (A␤) deposits and Tau tangles. More disputed is the observation that these mice accumulate intraneuronal A␤ that has been linked to synaptic dysfunction and cognitive deficits. Here, we provide immunohistological, genetic, and pharmacological evidences for early, age-dependent, and hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
191
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(219 citation statements)
references
References 90 publications
13
191
0
2
Order By: Relevance
“…The adverse impact of β-CTF on synaptic plasticity and neuronal function has attracted increasing interest (35,(41)(42)(43)(44)58). In our present studies, β-CTF, but not α-CTF, had detrimental effects on neuronal function, although they only differ in the first 16 N-terminal residues (see Methods).…”
Section: 8mentioning
confidence: 53%
See 2 more Smart Citations
“…The adverse impact of β-CTF on synaptic plasticity and neuronal function has attracted increasing interest (35,(41)(42)(43)(44)58). In our present studies, β-CTF, but not α-CTF, had detrimental effects on neuronal function, although they only differ in the first 16 N-terminal residues (see Methods).…”
Section: 8mentioning
confidence: 53%
“…The increase in Rab5 + puncta size was likely due to enhanced activation of Rab5, i.e., GTP-Rab5 (22), which induces homotypic fusion of early endosomes, causing their enlargement (19, 22, 23, Accumulation of β-CTF (C99) induces synaptic toxicity with a detrimental effect on neuronal function (41)(42)(43)(58)(59)(60). To explore whether C99-induced changes might be reflected in endosome structure and function, we tested APP SWE -YFP and APP M596V -YFP; expression of APP SWE provided a means to markedly increase C99 (57), while APP M596V enabled us examine the effect of full-length APP in the absence of C99 (57).…”
Section: Rab5mentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with these previous reports, the current study shows that the synaptic deficits observed in 3xTg‐AD mice at this early stage of the disease occur before the accumulation of plaques and tangles, suggesting that soluble oligomeric Aβ and phospho‐tau isoforms can induce profound synaptic deficits in 3xTg‐AD mice by 7‐8 months of age. Moreover, several studies have shown that the CTFs of APP are also important contributing factors leading to severe synaptic and memory deficits (Lauritzen et al., 2012). Similar to these studies, we found a profound increase in CTFs levels in hippocampal synaptosome samples from 7‐ to 8‐month‐old 3xTg‐AD mice, suggesting that the CTFs may have an important role in the synaptic impairments observed at this early age.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, unsuccessful efforts directed toward modifying Aβ production as a treatment for AD (Castello et al , 2014) have raised the possibility that other aspects of APP cleavage may be contributing to these metabolic changes. In this regard, increased levels of the C99 fragment have also been shown to contribute to AD pathogenesis (Lee et al , 2006; Lauritzen et al , 2012), suggesting a role for C99 in the early stages of pathogenesis.…”
Section: Introductionmentioning
confidence: 99%